Occupational Therapists' Perceived Preparedness to Work with Children Exposed to School Shootings. (3rd April 2022) - Scheidler, Bridget; Snyder, Karen; Carson, Nancy; Collins, Kayla
Abstract: The United States is witnessing a phenomenon of a rise in school shootings. Students exposed to school shootings often develop emotional disturbances negatively impacting the student's meaningful participation in daily activities. Occupational therapists are well positioned to address the needs of these students, yet little is known about occupational therapists' perceived self-efficacy as practitioners who may be called upon to address the unique needs of children who are exposed to school shootings. This phenomenological study explored the self-efficacy of occupational therapists who may encounter students exposed to a school shooting.